KEPRIBADIAN DAN PENATALAYAN EMOSI HAMBA TUHAN DI DALAM GEREJA - -, Chaliya Elisabet T; Rahayu, Esti (The Way: Jurnal Teologi dan Kependidikan, 2023)
This research aims to describe emotional stewardship, characteristics of healthy and unhealthy emotions, Biblical emotions, personality formation, personality traits and the correlation between personality and emotional stewardship. This research was conducted using descriptive qualitative methods. The research results reveal that a good steward is able to regulate his emotional condition in any condition and situation, and is responsible for it before God. A steward should have healthy emotions, namely not using God as an excuse to run away from Him, releasing negative emotions, accepting the impact of mistakes in the past to learn to be better in the future, living a balanced life between spirituality and the secular, always communing with God. Researchers emphasize that before someone is appointed as a steward in the church, it is better to have guidance both in terms of personality and emotions between fellow workers. Another alternative is to carry out a personality test so that you can find out what the characteristics of the steward are so that you can assess yourself and others. In this way, it is hoped that you will be able to be open to each other and accept the shortcomings and weaknesses of each worker. Researchers concluded that personality is able to influence someone in carrying out emotional stewardship.